2017
DOI: 10.1016/j.meegid.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Tunisian Leishmania major isolates causing human cutaneous leishmaniasis with contrasting clinical severity

Abstract: Zoonotic cutaneous Leishmaniasis caused by Leishmania (L.) major parasites affects urban and suburban areas in the center and south of Tunisia where the disease is endemo-epidemic. Several cases were reported in human patients for which infection due to L. major induced lesions with a broad range of severity. However, very little is known about the mechanisms underlying this diversity. Our hypothesis is that parasite genomic variability could, in addition to the host immunological background, contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Comparative genetic analysis of two different isolates of L. major from patients with contrasting severity of disease indicated that the hypo-virulent strain carried a mutated version of SAcP ( 170 ), suggesting a role of SAcP in virulence. Interestingly, a similar study looking at the genetic differences between two strains of L. donovani isolated from patients with cutaneous or visceral leishmaniasis, respectively, did not report a link between Leishmania AcPs and virulence ( 171 ).…”
Section: Leishmania Phosphatasesmentioning
confidence: 99%
“…Comparative genetic analysis of two different isolates of L. major from patients with contrasting severity of disease indicated that the hypo-virulent strain carried a mutated version of SAcP ( 170 ), suggesting a role of SAcP in virulence. Interestingly, a similar study looking at the genetic differences between two strains of L. donovani isolated from patients with cutaneous or visceral leishmaniasis, respectively, did not report a link between Leishmania AcPs and virulence ( 171 ).…”
Section: Leishmania Phosphatasesmentioning
confidence: 99%
“…This variability is probably related to sand fly vector(s) and/or animal reservoir(s) involved in transmission cycles ( Cupolillo et al., 2003 ) and with different clinical manifestations ( Quaresma et al., 2018 ; Rego et al., 2018 ). However, few studies have examined this variability in whole genomes of New-World Leishmania species, such as L. braziliensis ( Valdivia et al., 2015 ; Urrea et al., 2018 ; Bruna et al., 2019 ; Restrepo et al., 2019 ), because most of the research has focused on revealing the genome diversity of Old-World Leishmania species ( Downing et al., 2011 ; Imamura et al., 2016 ; Ghouila et al., 2017 ; Franssen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two fragments of 6535 and 4257 nucleotides belonging to the Leishmania braziliensis maxicircle were assembled [20], showing that despite the evolutionary divergence of L. braziliensis regarding other pathogenic Leishmania species [21], a remarkable conservation in the maxicircle gene ordering (synteny) was maintained. Now, when NGS technology is widely used for determining the nuclear genomic sequences of an increasing number of Leishmania species and strains [22,23,24,25,26,27,28,29,30,31,32], the time is coming to generate complete sequences of the mitochondrial genomes for the many Leishmania species named to date. In this work, we describe a pipeline designed to assemble the complete maxicircle sequences and the different minicircles by using the genomic NGS-reads generated during Leishmania nuclear genome sequencing.…”
Section: Introductionmentioning
confidence: 99%